Benefits of pregnancy classes on the independence of postpartum mothers in caring for newborns - Azizati Salmas Marsiami; Cynthia Puspariny; Wahyu Dwi Fatimah (Institute of Computer Science (IOCS), 2023)
The gestation and postpartum period is a period of high risk of psychological distress due to the adaptation of something new. The impact affects the onset of problems for postpartum mothers as well as the care of their babies. The class of expectant mothers is indispensable to prevent problems and complications. This study aims to determine the benefits of pregnant women's class on the independence of puerperal mothers in caring for newborns. This study used a Quasi-Experimental design with a two-group pretest-posttest design. The subjects of the study were pregnant women 32-36 weeks and postpartum mothers. The study's results using Mann Whitney obtained a P-value of 0.001 (≤0.05), meaning that pregnant women have a class benefit to the independence of puerperal mothers in caring for newborns. The class of pregnant women is very useful in increasing postpartum mothers' independence (knowledge and skills) in caring for their babies, such as bathing the baby, umbilical cord care, changing diapers, and feeding.